Economic Implications of Alternative Allocation Schemes for Emission Allowances: A Theoretical and Applied Analysis - Christoph Böhringer; Andreas Lange (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2003)
Political feasibility of emission trading systems may crucially depend on the free initial allocation of emission allowances to energy-intensive industries in order to ameliorate adverse production and employment effects. We investigate the potential trade-off between such compensation and economic efficiency for alternative allocation rules where emission allowances are based on either emissions or output. Based on analytical partial equilibrium and numerical general equilibrium analysis, we show that in open trading systems the trade-off becomes the more severe, the higher the international permit price is. Whenever the permit price can be considered exogenous to firms or industries, the output-based allocation rule is distinctly less costly than the emission-based rule to preserve output and employment in energy-intensive sectors. The reason is that emission-based allocation of allowances not only provides an implicit output subsidy but also lowers the effective price of emission inputs to regulated firms. Emissionbased allocation is particularly expensive towards higher international permit prices where the implicit subsidies to emission use in energy-intensive sectors produce drastic efficiency losses, since they imply high expenditures for carbon permit imports rather than high net revenues from efficient carbon permit exports.
Keywords: D58; H21; H23; 330; computable general equilibrium; emissions trading; allowance allocation; Umweltzertifikat; Umweltbelastung; Genehmigung; Allokation; Wirtschaftspolitische Wirkungsanalyse; Allgemeines Gleichgewicht; Theorie